Identifying shrines area using radarsat Lembah Bujang, Kedah, Malaysia - Mohd Noor, Norzailawati; Roslan, Shairatul Akma; Md Ali, Zuraini; Abdullah, Alias (2015)

(untitled)
Lembah Bujang was an international cultural and commercial crossroad 2000 years age. Its history, economic potential and a unique socio – cultural, art and architecture and diplomatic relationship offer fertile ground for scholar investigation. However, the issue on the pre-historic ruins as archaeological sites in Lembah Bujang were secretly demolished by modern development brings a further analysis. The aim for this research is to identify potential shrines area in two study areas consisting of Lembah Bujang and Kompleks Sungai Batu using RADARSAT images. Local Adaptive Filtering and Feature Extraction were applied to multi-temporal images of RADARSAT for years 2003 and 2014 to identify potential shrines. Two study areas were selected using ENVI 4.8. The findings show that The Local Adaptive Filtering on GAMMA Map filter is one of the best techniques in identifying potential shrines areas. This technique proves to be a reliable guide in historical sites detection in Malaysia which will also contribute to the chronological literature of the land use development planning in Lembah Bujang. Additionally, this technique will also aid in making recommendations for land use planning guidelines in preservation and conservation of heritage sites.